(3QSGdI GdGfJUGQ aj GdQO Ydi UGMH GdebGeI GdbQWHjIs - (3CHj LYaQ GHf CMeO, GdhRjQs
(3ChdgG (B:s
(3GdMeO ddg GdeJaQO HGdYRI hGdLdGdI , GdJhMjO HGdYXeI hGdceGd GdPi JYGdi Yf UaGJ GdYGdejf s
(3BNQgG (B:s
(3hbO hVY CjOg Gddg GdVjYg YfO ef jWjb MedgG hYfOgeG ef YghO GdCeQGA hcd eG aYdg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfis
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B4 - (3U (B27 s
(3eUOQ GbJfGA GdCUd (B:s
(3GSchQjGd (B(2/488) s
Keywords: (3GdCOHs